2018
DOI: 10.1111/jdi.12787
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between sodium–glucose cotransporter 2 inhibitors and pioglitazone as additions to insulin therapy in type 2 diabetes patients: A systematic review with an indirect comparison meta‐analysis

Abstract: Aims/IntroductionWe aimed to evaluate the efficacy and safety of pioglitazone (PIO) and sodium–glucose cotransporter 2 inhibitors (SGLT2i) as additions to insulin therapy for the management of type 2 diabetes mellitus.Materials and MethodsWe searched PubMed, EMBASE, the Cochrane Central Register of Controlled Trials and ClinicalTrials.gov through December 2016. Randomized controlled trials published in English that compared SGLT2i plus insulin (SGLT2i/INS) or PIO plus insulin (PIO/INS) with placebo plus insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
8
0
3
Order By: Relevance
“…In a comparative review by Singh and Singh, DPP-4 inhibitors plus insulin resulted in a 10-20% reduction in total daily insulin dose, whereas SGLT2 inhibitors plus insulin only resulted in a 0-10% reduction (21). A study comparing SGLT2 inhibitors with pioglitazone reported that combining both drugs with insulin therapy significantly decreased the insulin demand relative to the placebo; however, the difference in total daily insulin dose reduction between the two groups was not significant (19).…”
Section: Reduction In Daily Insulin Dosementioning
confidence: 99%
See 2 more Smart Citations
“…In a comparative review by Singh and Singh, DPP-4 inhibitors plus insulin resulted in a 10-20% reduction in total daily insulin dose, whereas SGLT2 inhibitors plus insulin only resulted in a 0-10% reduction (21). A study comparing SGLT2 inhibitors with pioglitazone reported that combining both drugs with insulin therapy significantly decreased the insulin demand relative to the placebo; however, the difference in total daily insulin dose reduction between the two groups was not significant (19).…”
Section: Reduction In Daily Insulin Dosementioning
confidence: 99%
“…By comparing SGLT2 inhibitors to DPP-4 inhibitors combined with insulin therapy for patients with T2D, a meta-analysis revealed that the former resulted in better glycemic control and lower levels of HbA1c [weighted mean difference (WMD) 0.24%, 95% CI 0.05-0.43] and FBG (WMD 18.0 mg/dl, 95% CI 7.6-28.5 mg/dl) than the latter (18). However, no significant difference was observed between SGLT2 inhibitors and pioglitazone plus insulin as treatment regimens for patients with T2D (19).…”
Section: Reduction In Hba1c and Fasting Blood Glucose Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects of SGLT2i might provide beneficial effects to suppress cardiovascular events, but the increased risk of hypoglycemia, and urinary tract and genital infection related to SGLT2i should be of note. Another study compared the impacts of SGLT2i with pioglitazone when added to insulin therapy in patients with type 2 diabetes with an indirect comparison meta‐analysis 11 . As the results, SGLT2i and pioglitazone achieved comparable reductions in HbA1c and fasting blood glucose, SGLT2i showed greater weight reduction, and pioglitazone achieved a higher reduction of daily insulin doses.…”
Section: Impacts Of Newly Developed Insulin Analogsmentioning
confidence: 99%
“…Results from studies comparing SGLT2is to active comparators added to insulin therapy provide compelling reasons for intensifying beyond basal insulin with SGLT2is. A network meta‐analysis of 14 12‐week or longer studies comparing SGLT2is and pioglitazone as add‐ons to insulin therapy revealed a similar HbA1c reduction in both groups, with the bonus of an additional 4.5 kg weight loss in the SGLT2i arm, despite lower end‐of‐study insulin doses with pioglitazone . When SGLT2is were evaluated in a network meta‐analysis against DPP‐4i as add‐on to insulin therapy in studies longer than 12 weeks, the SGLT2is were found to exert a 0.24% greater reduction in HbA1c than the DPP‐4i, and this was coupled with 2.4 kg more weight loss and similar incidences of hypoglycaemia …”
Section: Intensification With Dpp‐4i Glp‐1ra and Sglt2imentioning
confidence: 99%